2003
DOI: 10.1042/cs20020349
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with fish oil affects the association between very long-chain n-3 polyunsaturated fatty acids in serum non-esterified fatty acids and soluble vascular cell adhesion molecule-1

Abstract: We have investigated the effect of fish oil supplementation on the association between serum non-esterified fatty acid (NEFA) pattern and atherosclerotic activity. We studied correlations between serum non-esterified very long-chain eicosapentaenoic (EPA), docosahexaenoic acid (DHA) and arachidonic acid (AA) and biochemical markers of endothelial activation before and after 18-months intervention with fish oil supplementation. The fish oil supplementation consisted of 2.4 g of EPA and DHA per day, with corn oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…Hence, based on our results, we cannot attribute a beneficial effect to ALA or the marine fatty acids with regard to markers of endothelial integrity in healthy elderly. We do not think that the amount of ingested EPA/DHA in the present study was too low to induce an effect on endothelial markers, as other studies showed beneficial effects after low to moderate intakes of n-3 fish fatty acids Thies et al, 2001;Baro et al, 2003;Berstad et al, 2003;Hjerkinn et al, 2005). Our study duration was however shorter than those of other studies, which may have masked any beneficial effects of EPA/DHA on these endothelial markers.…”
Section: Discussioncontrasting
confidence: 57%
“…Hence, based on our results, we cannot attribute a beneficial effect to ALA or the marine fatty acids with regard to markers of endothelial integrity in healthy elderly. We do not think that the amount of ingested EPA/DHA in the present study was too low to induce an effect on endothelial markers, as other studies showed beneficial effects after low to moderate intakes of n-3 fish fatty acids Thies et al, 2001;Baro et al, 2003;Berstad et al, 2003;Hjerkinn et al, 2005). Our study duration was however shorter than those of other studies, which may have masked any beneficial effects of EPA/DHA on these endothelial markers.…”
Section: Discussioncontrasting
confidence: 57%
“…Alterations in the arachidonic acids system and lipid profiles (21), as well as reductions in the production of atherogenic cytokines, are thought to underlie the beneficial effects of eicosapentaenoic acid supplements (21,22). Eicosapentaenoic acid was found to decrease the plasma level of triglycerides, without affecting the plasma levels of total cholesterol and high-density lipoprotein cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent published clinical trial with n-3 fatty acids was performed by Berstad et al [13]. They divided a population with high risk of coronary heart disease into four intervention groups: fish oil supplementation, dietary intervention, fish oil supplementation plus dietary intervention, or placebo.…”
Section: N-3 Fatty Acids and The Endotheliummentioning
confidence: 99%